Erratum for: Raman amplified access networks with pump signal recycling for electrical power conversion. Issue 2 (February 2015) - Andre, P.S.; Lima, M. J. N.; Rocha, A. M.; Fernandes, N.; Granada, M.; Almeida, T.; Cang, Jin; Lan, Rao; Xiang‐Jun, Xin
ABSTRACT Nowadays, the structure of the passive optical networks is evolving, to keep the network survivability, the powering of some elements in this kind of networks is a key issue. In this work we propose the recycling of the Raman pump remaining optical power at the receiver to be converted to electrical power. With a 24 dBm optical pump signal a 8 dB on/off gain over 25 km of single mode optical fiber was achieved. Also, the recycling of the pump signal generated 18.1 mW of electrical power at the receiver. © 2011 Wiley Periodicals, Inc. Microwave Opt Technol Lett 54:116–119, 2012